Usable Object Management approaches for online social networks - Cheek, Gorrell P.; Shehab, Mohamed (Proceedings of the 2013 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining : ASONAM 2013 : Niagara Falls, Canada, August 25-28, 2013, 2013)
Online social networks have seen tremendous adoption and growth in recent years. Most attention, in access control literature, has been placed on abstracting and managing the large numbers of subjects or friends within these online social networks. Usable approaches for managing large amounts of objects, in the form of privacy information and content, have lagged. We introduce two approaches for object management. We extend our previous work to accommodate for object grouping and we introduce Same-As Object Management, which provides for a more usable object management approach that is effective, efficient and satisfying to the user. Same-As Object Management leverages a user's memory and perception of their objects for setting permissions for other similar objects. We implemented our model in an online social network and conducted a user study whose results are encouraging.